Identification of the Marketing Mix for Tourism Development at Jenon Spring - Supriono, Supriono; Prakasa, Yudha (IQTISHODUNA, 2025)
This study aims to identify the service marketing mix for tourism development in Jenon Spring (Sumberjenon), a natural tourist attraction in Gunungronggo Village, Tajinan District, Malang Regency, Indonesia. This descriptive qualitative study uses empirical data that has gone through a SWOT analysis to identify internal and external factors that may influence tourism development in Jenon Spring. Data sources come from interviews with the Mata Air Jenon destination manager, Village Apparatus, and Tourists. The results of the study indicate that the service marketing mix has a positive effect on the development of this tourist attraction and should be considered when determining and designing strategies to develop the tourist attraction in attracting potential tourists. The results also found that support from other related parties, including the government, private institutions, and the community is essential. However, several weaknesses were also identified, including security, safety, and human resources. The unique traditions of the local community in Jenon Spring are strong development opportunities, while competition with other similar tourist attractions and weather-related constraints were identified as possible threats.